ANALISIS PENERAPAN TAX AMNESTY TERHADAP PENERIMAAN DAERAH YANG DIMODERASI OLEH PENINGKATAN KEPATUHAN WAJIB PAJAK - Nova, Nisa Khaerin (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Taxes are the main source of state revenue, but tax revenues are still considered not optimal. Therefore, through the Directorate General of Taxation, the government continues to make breakthroughs to optimize revenue in this sector. One of the policies set by the Directorate General of Taxation is Tax Amnesty. Tax amnesty carried out by the government can be used as an effort to increase taxpayer compliance so that it can collect state revenues from the tax sector quickly within a predetermined period. This study aims to analyze the implementation of the tax amnesty policy with an increase in regional revenues mediated by an increase in taxpayer compliance. This research was conducted at the Tax Office Pratama Bandung with descriptive research methods, verification, with the Multiple Regression approach. Primary data source, data collection technique through a closed questionnaire. The Sampling technique is Non-probability Sampling with saturated sample technique. The results of the study show that the tax amnesty has not been able to increase regional revenue in Bandung, but increases taxpayer compliance. Furthermore, with moderation, taxpayer compliance can increase local revenue